Linguistic personality of Ivan Franko in the matrimonial directive discourse - Трумко, Оксана Михайлівна (The Journal of V. N. Karazin Kharkiv National University. Series “Philology”, 2020)
The purpose of this article is to reveal specific features of the realization of the linguistic personality of I. Franko in the matrimonial directive discourse. The source base for the analysis was I. Franko’s letters to O. Khoruzhynskaya. The analysis of I. Franko's linguistic personality done within a cognitive-discursive paradigm, using discourse-analysis, intent-analysis, contextual analysis, methods of analysis and synthesis, descriptive method. Іt was established that the intension of directive in the speech of I. Franko was aimed at the expression of advice, requests and questions. The writer seeks a positive settlement at regulating his wife’s health problems, her life and scientific work, financial issues. It also prompts the wife to take care of oneself and children, to perform / not to perform certain actions towards him / other persons, to write a work or to engage in literary activities of family’s acquaintances. I. Franko asks wife to determine his further actions in certain everyday situations. The question is a means of getting new information about the wife's daily affairs, the children’s health state, domestic problems, weather conditions, common friends or the reasons for the absence of letters from his wife. I. Franko uses a question for reconciling family planning. Linguistic means: declarative, imperative and interrogative / interrogative-imperative sentences, verbs of the imperative / conditional mood, imperative verbs together with the infinitive / negative particle not, the verb ask in the 1st person singular, personal pronouns, adverbs, restrictive / emphatic particles and exclamation, etc. Complex sentences provide expressions of incentives and their argumentation. The speech is characterized by obsolete / colloquial words, dialecticisms, polonizms, russisms and chekhisms. The writer uses phraseologisms, metaphors, similes, words in figurative meaning. Terms of endearment and means of expressing courtesy show favor to the addressee. Consequently, the directive discourse ensures the realization of Ivan Franko’s linguistic personality in family communication on the motivational, linguistic-cognitive and lexico-grammatical levels.